2017
DOI: 10.1016/j.spl.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A modification of balanced acceptance sampling

Abstract: This article presents a modification of balanced acceptance sampling (BAS) that causes inclusion probabilities to better approximate targeted inclusion probabilities. A new sample frame constructor for BAS is also introduced from which equi-probable spatially balanced samples are drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In addition to reducing costs compared to traditional LPI methods, Cagney et al () highlighted that images provide a permanent record, which can be reevaluated if data are questionable, if software improves, or if management objectives change. Here, we add a spatially balanced sampling design, called balanced acceptance sampling (BAS) (Robertson et al , ), along with geo‐tagged imagery, to sample reclaimed natural gas well pads and reference sites. BAS is a representative sample of the population from which it is drawn (Robertson et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reducing costs compared to traditional LPI methods, Cagney et al () highlighted that images provide a permanent record, which can be reevaluated if data are questionable, if software improves, or if management objectives change. Here, we add a spatially balanced sampling design, called balanced acceptance sampling (BAS) (Robertson et al , ), along with geo‐tagged imagery, to sample reclaimed natural gas well pads and reference sites. BAS is a representative sample of the population from which it is drawn (Robertson et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The i th coordinate of each point in the sequence has an associated base bi, with b1=2 and b2=3. The i th coordinate of the k th point in this sequence is (Robertson, McDonald, Price, & Brown, )xk(i)=j=0⌋⌊ui+kbij0.333333emmod0.333333embi1b0.166667emij+1,where ui is a random non‐negative integer and ⌊ x ⌋ is the floor function — the largest integer that is less than or equal to x . For example, the first coordinate of the second point with u1=1 and b1=2 isx2false(1false)=⌋⌊310.333333emmod0.333333em212+⌋⌊320.333333emmod0.333333em214+⌋⌊340.333333emmod0.333333em218=12+14+0=34.…”
Section: Methodsmentioning
confidence: 99%
“…If x1 is not in the study area, new sequences are considered until one with x1 in the study area is found (Robertson et al., ). Starting from x1, the first n scaled points in the study area define the BAS sample (Robertson et al., ). The BAS points are kept in the same order as they appear in Equation and will have good spatial spread over the study area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations